Numerical Methodology to Obtain the Sound Absorption of Materials by Inserting the Acoustic Impedance - BORGES MENDES, Cláudia Ohana; DE ARAÚJO NUNES, Maria Alzira (Archives of Acoustics, 2021)
Numerical models allow structural characteristics to be obtained by solving mathematical formulations. The sound absorption capacity of a material can be acquired by numerically simulating an impedance tube and using the method governed by ISO 10534-2. This study presents a procedure of obtaining sound pressure using two microphones and as outline condition, at one end of the tube, the impedance of fiber samples extracted from the pseudostem of banana plants. The numerical methodology was conducted in the ANSYS® Workbench software. The sound absorption coefficient was obtained in the MATLAB® software using as input data the sound pressure captured in the microphones and applying the mathematical formulations exposed in this study. For the validation of the numerical model, the results were compared with the sound absorption coefficients of the fiber sample collected from an experimental procedure and also with the results of a microperforated panel developed by Maa (1998). According to the results, the methodology presented in this study showed effective results, since the largest absolute and relative errors were 0.001 and 3.162%, respectively.